Chipless RFID tags and sensors: a review on time-domain techniques. Issue 2 (2nd October 2015) - Forouzandeh, Mohammadali; Karmakar, Nemai Chandra
Abstract : In the past few years Radio Frequency Identification ( RFID ) has grown to be one of the most popular technologies in the area of identification systems. Following a brief survey of RFID systems, this paper provides a technical review of work undertaken in the field of time-domain chipless RFID tags and sensors. This paper aims not only to address the chipless tags which use Time Domain Reflectometry (TDR) concept for data encoding but also for the use of Ultra-Wideband Impulse-Radar (UWB-IR) as a time-domain measurement technique. The penultimate section intends to focus on time-domain reading setups and finally, a brief comparison between this method and other chipless techniques is provided.